68Ga-PSMA-11 PET/CT in primary and recurrent prostate carcinoma: implications for radiotherapeutic management in 121 patients - Körber, Stefan A.; Will, Leon; Kratochwil, Clemens; Häfner, Matthias; Rathke, Hendrik; Kremer, Christophe; Merkle, Jonas; Herfarth, Klaus; Haberkorn, Uwe; Debus, Jürgen; Giesel, Frederik L. (Journal of nuclear medicine, 2019)
The present study analyzed the impact of Gallium-68 (68Ga)-labeled prostate-specific membrane antigen-HBED-CC (68Ga-PSMA-11) positron-emission tomography (PET)/computed tomography (CT) on radiotherapeutic management in a large cohort of men with primary or recurrent disease. Methods: This study investigated 121 men with carcinoma of the prostate who underwent 68Ga-PSMA-11 PET/CT as well as conventional imaging. 50 patients were treatment naive, 11 had persistent prostate-specific antigen (PSA) soon after surgery and 60 presented with recurrent PSA following definitive therapy. Changes in TNM classification of malignant tumors (TNM) stage and radiotherapeutic management after 68Ga-PSMA-11 imaging were compared to results achieved with conventional imaging. Results: In total, a change in TNM stage and radiotherapeutic management was observed for 49 patients (40.5%) and 62 patients (51.2%), respectively. In treatment naïve patients, a change in TNM stage and radiotheraeutic plan occurred in 26.0% and 44.0% of the cohort respectively. For patients with PSA persistence or recurrence, TNM and radiotherapeutic management changed in 50.7% and 56.3% respectively. Conclusion: 68Ga-PSMA-11 PET/CT may shortly become an indispensable tool for detecting prostate cancer lesions in treatment-naïve patients as well as in men with recurrent disease or persistent PSA and seems to be very helpful in personalizing radiotherapeutic management to the individual patients’ distribution of disease.
Published on July 5, 2018
Im Titel ist "68" in 68Ga-PSMA-11 PET/CT hochgestellt
Gesehen am 12.03.2019